Enric Miralles’ Architectural Pieces: Three Exemplary Attempts - Vela, José (ZARCH, 2016)
The status of an “unbuilt idea” is a dubious one. It presupposes, in the first place, the existence of something as elusive as “architectural ideas”. Moreover, it disconnects architectural thinking from its materialization, either implying that ideas are not embedded in architecture only or that architecture can only be found in built buildings —erasing the ideas in the process. Finally, it takes away from architecture its capacity of awakening, of production versus mere reproduction. Of course, none of these assertions are quite right –though none are totally untrue. This paper will explore three architectural pieces designed by architect Enric Miralles around the mid-1990s in search not of an answer to the abovementioned questions —which will be impossible in the limited amount of space of this article— but of a demonstration, in the sense of a presentation, of the complexity of the task. Three architectural pieces radically different but nevertheless coherent as a group, of a rather uncanny quality —being architecture, are neither buildings nor ideas— will be presented in their exemplar quality: they are exemplar —even paradigmatic— constructions precisely because they are not buildings and remain unbuilt. No conclusions should be expected, even if the endeavor is worth the attempt.